Fluid-mediated metal transport in subduction zones and its link to arc-related giant ore deposits: Constraints from a sulfide-bearing HP vein in lawsonite eclogite (Tianshan, China). - Li, Jilei; Gao, Jun; John, Timm; Klemd, Reiner; Su, Wen (Geochimica Et Cosmochimica Acta, 2013)
High-pressure (HP) veins in eclogites provide insight into element mobility during fluid-rock interaction in subduction zones. Here, we present a petrological-geochemical study of a sulfide-bearing HP vein and its massive lawsonite eclogite host rock from the Chinese Tianshan (ultra-)high-pressure/low-temperature metamorphic belt. The omphacite-dominated vein is enveloped by a garnet-poor, sulfide-bearing eclogite-facies reaction selvage. Lawsonite, garnet, omphacite, glaucophane and other HP minerals occur as inclusions in pyrite porphyroblasts of the selvage rock, indicating that the selvage formed prograde under eclogite-facies conditions. Relicts of wall-rock garnet (Grt_I) cores in recrystallized selvage garnet (Grt_II) close to the wall rock and the Ca distribution in Grt_II, which images the overgrown selvage matrix, indicate that the selvage formed due to dissolution-precipitation processes as a consequence of fluid-rock interaction of the wall rock eclogite with the vein-forming fluid. The peak metamorphic P-T conditions of the wall-rock eclogite are estimated at ca. 590. °C and 23. kbar. Mass-balance calculations indicate that the reaction selvage experienced: (1) a depletion of the large-ion lithophile elements (K-Rb-Ba) of up to 100% relative to their concentrations in the wall-rock eclogite; (2) a moderate depletion of the HREE and some transition metal elements including Fe, Cu, Ni, Zn, Co, Cr, and Mn (10-40%); (3) a significant enrichment of CaO (up to 50-80%), Sr (up to 200%), Pb (up to 170%) and S (up to 210%); (4) a slight to moderate enrichment of the LREE (10-20%) and MREE (0-40%); whereas (5) the HFSE show no significant variations.The chemical changes in the selvage suggest that the fluid, which caused the dissolution of the wall-rock and the precipitation of the selvage assemblage while the vein formed, was probably a mixture of an "internal" fluid derived from the prograde dehydration (e.g., lawsonite breakdown) of the wall rock and an "external" fluid most likely derived from dehydrating altered oceanic crust located in stratigraphically lower units of the subducting slab. The external fluid introduced Ca, S, Sr, Pb and at least parts of the LREE and the MREE into the selvage, whereas some elements, such as the remaining LREE and MREE, may have been derived from the wall rock eclogite via diffusional transport into the selvage. The enrichment of Ca and L-MREE is displayed by the abundant growth of selvage epidote. In contrast, the dissolution of garnet and phengite released significant amounts of HREE and LILE (K-Rb-Ba) into the passing fluid, because the chemical changes within the selvage prevented the formation of a mineral assemblage with sufficiently high bulk-fluid partition coefficients for these elements. Significant amounts of transitional metal elements were released into the fluid during the dissolution of white mica and the dissolution-precipitation behavior of garnet, omphacite, dolomite and sulfides. Thus the LILE and HREE along with some transition metal elements (e.g., Fe, Cu, Ni and Zn) were mobilized during the dissolution-precipitation processes that led to the selvage formation. Accordingly the slab fluids are not only strongly enriched in LILE and depleted in HFSE, but also carry significant amounts of transition metals. It is most likely that slab fluids strongly contribute to the metal flux into the arc magma systems finally resulting in giant arc-related ore deposits. © 2013 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.c3geoc.fluidm